A whiter shade of pale: anchoring the name Paecilaema C. L. Koch, 1839 onto a neotype (Opiliones, Cosmetidae) - Kury, Adriano B.; Medrano, Miguel (Zootaxa, 2018)
The generic name Paecilaema C.L. Koch, 1839 is anchored to the nomen dubium Cosmetus u-flavum Perty, 1833, and the fixation of the latter is proposed by designating a neotype. The choice was made on a potential topotype, being a common species in metropolitan Rio de Janeiro city, SE Brazil, which has been described as new five times and is currently best known as Metavononoides bellus (Mello-Leitão, 1932). Cosmetus u-flavum has been originally included in Paecilaema along with Paecilaema limbatum Kollar in C.L. Koch, 1839, the latter here synonymized with the former. Therefore, our choice of this species is adequate in conveying Koch’s original concept of Paecilaema. The most striking diagnostic feature of the species of Paecilaema is the presence of a lyra, a unique shape of blots in layers of shades of white to pale yellow on the dorsal scutum. Other patterns of scutal white blots are hereby defined and named. Paecilaema is here considered most closely related to Metavononoides Roewer, 1928. Comments are made on the diagnostic characters and the terminology of parts of the lyra is expanded with the introduction of new terms. Comments are made on the formation of the generic name Paecilaema. Taxonomic adjustments are made in the closest relatives of Paecilaema u-flavum, and the following nomenclatural acts are proposed: (1) MNRJ 3433 is designated as male neotype of Cosmetus u-flavum, type species of Paecilaema. (2) Proposed new synonymies: Poecilaema soerenseni Henriksen, 1932 = Paecilaemula bella Mello-Leitão, 1932 = Eucynorta brasiliensis Mello-Leitão, 1923 = Paecilaema limbatum Kollar in C.L. Koch, 1839 = Cosmetus u-flavum Perty, 1833. (3) Nine species originally described elsewhere but currently placed in Metavononoides are transferred to Paecilaema, either as new or as restored combinations: Paecilaemula albisecta Mello-Leitão, 1942, Poecilaemula albosigillata Mello-Leitão, 1941, Paecilaema lyra Sørensen, 1932, Metavononoides melanacanthus Ferreira, Pedroso & Kury, 2005, Paecilaema muticum Sørensen, 1932, Paecilaema ornatissimum Mello-Leitão 1942, Poecilaemula peculiare Roewer, 1917, Paecilaemula preciosa Roewer 1928 and Metavononoides renneri Ferreira, Pedroso & Kury, 2007. (4) The following genera, currently in the synonymy of Paecilaema, are all revalidated and given emended diagnoses: Meterginoides Roewer, 1912, Meterginulus Roewer, 1912, Paecilaemella Roewer, 1925, Pararhauculus Roewer, 1933, Soaresella Goodnight & Goodnight 1947. (5) Their respective type species, currently combined under Paecilaema, are transferred back to their revalidated genera: Paecilaema rastelliferum Pickard-Cambridge 1905 to Meterginulus; Meterginus inermis Banks, 1909 to Meterginoides; Pararhauculus lineatus Roewer, 1933 to Pararhauculus; Paecilaemella festae Roewer, 1925 to Paecilaemella and Soaresella gracilis Goodnight & Goodnight, 1947 to Soaresella.